Gene targeting in Silkworm (Bombyx mori) by Engineered Endonucleases - Sajwan, Suresh Chandra Singh (Jihočeská univerzita, 2013)
This thesis describes the establishment of a precise gene targeting methodology in the silkworm Bombyx mori by technologies based on engineered endonucleases. Two classes of engineered endonucleases, ZFNs and full length TALENs were used for creating DSBs at specified sites in the colour marker genes (BmBlos2 and Bmwh3). Direct embryo microinjection of engineered nucleases mRNA were performed and let the nuclease proteins to disrupt the functions of these marker genes by creating DSBs and inducing error prone NHEJ mechanism. These experiments showed that both ZFNs and TALENs could be used for targeted gene disruption in silkworms.
Gene targeting in Silkworm (Bombyx mori) by Engineered Endonucleases
Keywords: Gene targeting; ZFN; Nonhomologous end joining; MMEJ; BmBLOS2; Chimeric nucleases; Lepidoptera; BmBLOS2; Bm1 element; Gene targeting; ZFN; Nonhomologous end joining; MMEJ; BmBLOS2; Chimeric nucleases; Lepidoptera; BmBLOS2; Bm1 element